2012
DOI: 10.1128/jvi.01717-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for pH-Dependent Protease Activity in the Adeno-Associated Virus Capsid

Abstract: Incubation of highly purified adeno-associated virus (AAV) capsids in vitro at pH 5.5 induced significant autocleavage of capsid proteins at several amino acid positions. No autocleavage was seen at pH 7.5. Examination of other AAV serotypes showed at least two different pH-induced cleavage patterns, suggesting that different serotypes have evolved alternative protease cleavage sites. In contrast, incubation of AAV serotypes with an external protease substrate showed that purified AAV capsid preparations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Our data suggest that at neutral pH, this region is not highly dynamic, raising the possibility that the role of autohydrolysis is to increase dynamics around the 5-fold axis during trafficking. Our results support the hypothesis that proteolysis is a trigger for externalization of VP1u, as was also recently suggested based on the identification of a protease function in AAV2 (39).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our data suggest that at neutral pH, this region is not highly dynamic, raising the possibility that the role of autohydrolysis is to increase dynamics around the 5-fold axis during trafficking. Our results support the hypothesis that proteolysis is a trigger for externalization of VP1u, as was also recently suggested based on the identification of a protease function in AAV2 (39).…”
Section: Discussionsupporting
confidence: 80%
“…An additional factor that must be considered is autohydrolysis of AAV VPs. This was recently described for nine of the AAV serotypes (39). Bands originating from the degradation of VPs increase with time on SDS-PAGE gels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that the previous study utilized AAV2 virions that had not gone through physiological endosomal processing, allowing for the conformational change that exposes the basic regions along with the PLA2 domain required for transduction. A recent study by Salganik et al showed that purified AAV2 virions have external protease activity at physiological pH that is ablated at low pH (76). It is possible that virions that traffic to the nucleus using alternative pathways can exert alternative functions, such as proteasemediated, NPC-independent nuclear entry under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Small differences in the structures and dynamics of various parvovirus and adeno-associated virus (AAV) capsids have been reported (35,47,48). Although the crystal structures of empty particles or virus-like particles (VLPs) appear structurally highly similar to those of infectious DNA-containing capsids when different crystal structures are compared, some differences in the structures and dynamics have been revealed (49)(50)(51).…”
mentioning
confidence: 99%